2022
DOI: 10.1111/1475-6765.12509
|View full text |Cite
|
Sign up to set email alerts
|

Populism and intra‐party democracy

Abstract: This article examines how populism is linked to party organization and, specifically, intra-party democracy. Populism can be defined as an ideology (ideational perspective), which is characterized by anti-elitism, people-centrism and a discourse emphasizing a moral struggle between 'good people' and 'the elite'. On the other hand, there are leadership-focused definitions which see populism as a form of organization with personalistic control (a leadership perspective). With respect to party organization, focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…On the road from conservatism to populism, Fidesz became hostage of its party leader (Körösényi, 2007(Körösényi, , 2019. This image of party organization confirms former scholarly analysis that party democracy is missing in leadercentred populist parties (Böhmelt et al 2022). This organizational transformation was going in parallel with Fidesz's changed political and policy attention in a populist frame and changed the conflict structure towards the GAL/TAN divide (see Table 6.1b).…”
Section: The Party System and The Main Actorssupporting
confidence: 59%
“…On the road from conservatism to populism, Fidesz became hostage of its party leader (Körösényi, 2007(Körösényi, , 2019. This image of party organization confirms former scholarly analysis that party democracy is missing in leadercentred populist parties (Böhmelt et al 2022). This organizational transformation was going in parallel with Fidesz's changed political and policy attention in a populist frame and changed the conflict structure towards the GAL/TAN divide (see Table 6.1b).…”
Section: The Party System and The Main Actorssupporting
confidence: 59%
“…To qualify populist parties, we rely on Mudde's (2007) well‐established definition conceiving populism as a ‘thin ideology’ not expressing core beliefs, but conceiving that society is divided into two homogeneous and antagonistic groups, the ‘pure people’ versus the ‘corrupt elite’. By emphasizing anti‐elitism, people‐centrism and moral integrity (Böhmelt et al ., 2022), recent research has identified parties for which populism is a constitutive ideational element (Zulianello, 2020). For the purpose of this study, this ideational approach allows the conceptualization of party's populist views and discourses as informal rules guiding behaviour.…”
Section: Theoretical Framework: Institutions and Legislative Behaviourmentioning
confidence: 99%